A CRITICAL ANALYSIS OF MARKETING STRATEGIES IN ENHANCING THE COMPETITIVE ADVANTAGE OF CAFE PONDOK REZEKI DELI TUA - Purnama Sari; Ratih Amelia; Jessica Andre; Tina Linda; Ahmad Fadli (Yayasan Bina Bisnis Nusantara Medan, 2025)
Marketing strategy plays a crucial role in influencing the success and competitiveness of a business. Effective marketing strategies enhance a company's ability to expand its market share and achieve desired profitability. This study aims to identify appropriate marketing strategies for Cafe Pondok Rezeki Deli Tua to strengthen its competitive advantage. A descriptive qualitative approach was employed, utilizing SWOT analysis through the Internal Factor Analysis Summary (IFAS) and External Factor Analysis Summary (EFAS) matrices. The findings reveal that a Growth-Oriented Strategy is the most suitable approach, as the business is positioned in Quadrant I with positive results. It is recommended that Cafe Pondok Rezeki Deli Tua further enhance its marketing efforts, particularly focusing on the marketing mix elements, to effectively compete with other cafés in the region.